Holy communion in contagious times - T. E. Ncapodi (Acta Theologica)
Richard Burridge’s volume could not have come at a better time. In the aftermath of the COVID pandemic, his discourse is on the virtual church and the celebration of Holy Communion online. Some Christian churches have gladly embraced the concept of online meetings and still allow their members to attend services in this way. Other Christian churches do not support online Holy Communion. Instead, they support online church services only, without the Eucharist. Burridge’s book provides a raison d’etre for online forms of Christian worship.